2011
DOI: 10.4088/pcc.10m01050
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome in Obese Patients With Binge-Eating Disorder in Primary Care Clinics

Abstract: Metabolic syndrome is common in obese patients with BED in primary care settings and is associated with fewer dieting behaviors. These findings suggest that certain lifestyle behaviors, such as increased dietary restriction, may be potential targets for intervention with metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
2
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 36 publications
5
23
2
3
Order By: Relevance
“…A large percentage of individuals with BED (>40%) meet the criteria for metabolic syndrome 69,70. Consistent with this finding, in a 5-year longitudinal study, individuals with BED who were obese were found to be at increased risk for developing components of metabolic syndrome compared with individuals without BED who were BMI-matched to those with BED 74.…”
Section: Evidence Base For Factors Not Included As Diagnostic Criteriasupporting
confidence: 54%
“…A large percentage of individuals with BED (>40%) meet the criteria for metabolic syndrome 69,70. Consistent with this finding, in a 5-year longitudinal study, individuals with BED who were obese were found to be at increased risk for developing components of metabolic syndrome compared with individuals without BED who were BMI-matched to those with BED 74.…”
Section: Evidence Base For Factors Not Included As Diagnostic Criteriasupporting
confidence: 54%
“…Premenopausal women were also less likely to show clinically elevated glucose level. Thus, obese men with BED may be at increased risk for MetS, which is consistent with our previous studies with treatment-seeking individuals with BED (Barnes, et al, 2011; Roehrig, et al, 2009). In our study, women overall reported significantly earlier onset of dieting than men.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, in obese individuals with BED, the rate of MetS has been found higher in men than women (Barnes, et al, 2011; Roehrig, et al, 2009). Yet, age-matched sex comparison of the risk for MetS has not been investigated in this population.…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic syndrome was defined by the National Cholesterol Education Program Adult Treatment Panel III (ATP III) and updated in 2005 by the American Heart Association and the National Heart Lung and Blood Institute (See Table 1) (Grundy et al, 2005; National Cholesterol Education Program Expert Panel, 2002). Participants’ medication use was not assessed at post-treatment so diagnosis was based solely on objective measurements, consistent with some previous BED and metabolic syndrome literature (Barnes et al, 2011; Blomquist et al, 2012). Based on these criteria, 35.1% ( n =26) met criteria for metabolic syndrome.…”
Section: 1 Materials and Methodsmentioning
confidence: 98%
“…In fact, a longitudinal study reported individuals who reported binge eating were at greater risk for newly diagnosed metabolic syndrome symptoms, compared with non-binge eaters (Hudson et al, 2010). Consequently, individuals with BED and excess weight have been underscored as a significant subgroup with increased risk for developing metabolic syndrome (Abraham, Massaro, Hoffmann, Yanovski, & Fox, 2014; Barnes et al, 2011; Blomquist et al, 2012; Hudson, Hiripi, Pope, & Kessler, 2007; Mitchell, 2015; Sheehan & Herman, 2015; Udo, McKee, White, Masheb, Barnes, & Grilo, 2014a; Udo, McKee, White, Masheb, Barnes, & Grilo, 2014b). It is critical, therefore, to examine these individuals, with excess weight, metabolic syndrome, and binge eating disorder, as they may be at extreme risk for harmful health-related consequences.…”
Section: 1 Introductionmentioning
confidence: 99%